Impact of Social Change on Effective Communication in Indonesia: Dampak Perubahan Sosial terhadap Komunikasi Efektif di Indonesia - Wijayanti, Novita Fitri; Ardina, Navira Vriska; Shakinah, Shaffira Bella; Abadi , Totok Wahyu (Universitas Muhammadiyah Sidoarjo, 2024)
This study examines the impact of social change on effective communication within communities, highlighting the importance of communication for both individuals and organizations. Using bibliometric analysis with VOSviewer, the research visualized interconnected authors and keyword frequency, revealing that effective communication is crucial in preventing issues caused by poor communication. The findings suggest that developing good communication skills benefits both individuals and their communities, and that managing social changes can mitigate negative impacts by filtering cultural influence. Highlights: Communication skills are essential for individuals and organizations. Bibliometric analysis visualizes author connections and keyword frequency. Managing social change helps mitigate negative cultural influences. Keywords: Social change, effective communication, bibliometric analysis, VOSviewer, community impact